2017
DOI: 10.1002/mp.12585
|View full text |Cite
|
Sign up to set email alerts
|

Integrating prior information into microwave tomography Part 1: Impact of detail on image quality

Abstract: Including knowledge of the breast surface and skin layer leads to a substantial improvement in image quality compared to the blind case, but the images have limited diagnostic utility for applications such as tumor response tracking. The diagnostic utility of the reconstruction technique is improved considerably when patient-specific structural information is used. This qualitative observation is supported quantitatively with image metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 47 publications
(60 reference statements)
1
57
0
Order By: Relevance
“…In the context of microwave tomography, we have collaborated with the Electromagnetic Imaging Laboratory at the University of Manitoba to investigate the impact of incorporating surface estimates in the reconstruction algorithm. The results of the study are reported in [ 14 ] (e.g., Figure 17 page 12). Without the breast surface incorporated into the image domain, internal structures are not clearly resolved.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of microwave tomography, we have collaborated with the Electromagnetic Imaging Laboratory at the University of Manitoba to investigate the impact of incorporating surface estimates in the reconstruction algorithm. The results of the study are reported in [ 14 ] (e.g., Figure 17 page 12). Without the breast surface incorporated into the image domain, internal structures are not clearly resolved.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, these data are absent from the original set of measurements. The tessellation algorithm [ 21 ] is applied to the point cloud to produce a surface mesh shown in Figure 15 c that may be incorporated into an image reconstruction algorithm to form backscatter energy images [ 3 ], or dielectric property maps [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations